2012
DOI: 10.2147/pgpm.s23422
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic considerations in opioid analgesia

Abstract: Translating pharmacogenetics to clinical practice has been particularly challenging in the context of pain, due to the complexity of this multifaceted phenotype and the overall subjective nature of pain perception and response to analgesia. Overall, numerous genes involved with the pharmacokinetics and dynamics of opioids response are candidate genes in the context of opioid analgesia. The clinical relevance of CYP2D6 genotyping to predict analgesic outcomes is still relatively unknown; the two extremes in CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 161 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…These metabolites are removed by the kidneys, therefore, in kidney disease patients’, metabolite concentration may be high and may lead to adverse events [8,18]. A multiple regression analysis, presented maximum pain score as the crucial factor contributing to morphine usage, followed by ethnicity and A118G polymorphism [19]. Advanced cancer patients who suffered pain caused by homozygosity for the 118G allele of the μ-opioid receptor required higher morphine doses to achieve successful pain control.…”
Section: Pain Medication Opioid Analgesics and Non-steroidal Antimentioning
confidence: 99%
See 1 more Smart Citation
“…These metabolites are removed by the kidneys, therefore, in kidney disease patients’, metabolite concentration may be high and may lead to adverse events [8,18]. A multiple regression analysis, presented maximum pain score as the crucial factor contributing to morphine usage, followed by ethnicity and A118G polymorphism [19]. Advanced cancer patients who suffered pain caused by homozygosity for the 118G allele of the μ-opioid receptor required higher morphine doses to achieve successful pain control.…”
Section: Pain Medication Opioid Analgesics and Non-steroidal Antimentioning
confidence: 99%
“…A common polymorphism of OPRM1 is a single nucleotide substitution at position 118, where an adenine is substituted for a guanine (A118G). It was reported that among Caucasians these substitutions occur with an allelic frequency of 10%–30%, with a higher prevalence amongst Asians, and a lower in African Americans [19]. The binding affinity for b-endorphin is increased with this polymorphism, which results in the change of an amino acid (asparagine for aspartate).…”
Section: Enzymes Involved In Drug Metabolismmentioning
confidence: 99%
“…1,2 In pain management specifically, PGT can guide personalized treatment plans, identify medication metabolism abnormalities, clarify and validate urine drug testing (UDT) results, help clinicians avoid potential medication interactions, and guide therapeutic decision-making such as dose adjustments, changes in medication dose, or opioid rotation. [3][4][5][6][7][8] This information, combined with general risk assessment strategies, a thorough history and physical examination, knowledge of potential concomitant medication interactions, and urine drug testing, can improve understanding of the unique and highly individualized responses to treatment so often seen in specialty care settings.…”
Section: Introductionmentioning
confidence: 99%
“…Val158 alleles may also be associated with an advantage in the processing of aversive stimuli, or pain. Individuals who are homozygous for the Met158 allele show increased pain sensitivity, likely through a lower-functioning μ-opioid system response to prolonged pain 104,105. A cohort study investigating repeated thermal-pain stimulation both before and after one single dose of opiate in caucasions showed that individuals with the Val158 genotype did not respond to either the initial noxious stimulus or the analgesic response to remifentanil 106.…”
Section: Genetic Polymorphisms Associated With Drugs Used To Treat Painmentioning
confidence: 99%